Sol Sirkumflex Arterden Köken Alan Sağ Koroner Arter Anomalili Hastada Akut Miyokard İnfarktüsü: Olgu Sunumu - Karaca, Özkan; Karasu, Mehdi; Yavuz, Doğukan Yasin; Mirzaoğlu, Çetin; Doğdu, Orhan (Rabia YILMAZ, 2017)
Sağ koroner arterin, Sol sirkumflex arterin (LCX) distalinden çıkması nadir görülen bir anomalidir. Ani ölüm gibi tehlikeli klinik durumlara yol açabildiğinden tanınması önemlidir. Bu yazıda, sol sirkumflex arterden köken alan sağ koroner arter anomalisi olan 52 yaşında erkek hastada gelişen akut inferoposterior sağ miyokardial infarktüs olgusu sunduk.

Origin of the Right anterior descending artery  from the Left Circumflex artery (LCX) is the rarely seen  anotomic varıation of this coronary artery. It is important to recognize because it can lead to dangerous clinical situations such as sudden death. In this report, we presented a case of 52 years old male acute inferoposterior myocardial  infarction in patient with anomaly of right coronary artery originating from left circumflex artery.
Acut Myocardial Infarction in Patient with Anomaly of Right Coronary Artery Originating from Left Circumflex Artery: A Case Report
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi